Organotypic Cultures as a Model to Study Adult Neurogenesis in CNS Disorders - Fabio Cavaliere; Monica Benito-Muñoz; Carlos Matute (Stem Cells International)
Neural regeneration resides in certain specific regions of adult CNS. Adult neurogenesis occurs throughout life, especially from the subgranular zone of hippocampus and the subventricular zone, and can be modulated in physiological and pathological conditions. Numerous techniques and animal models have been developed to demonstrate and observe neural regeneration but, in order to study the molecular and cellular mechanisms and to characterize multiple types of cell populations involved in the activation of neurogenesis and gliogenesis, investigators have to turn to in vitro models. Organotypic cultures best recapitulate the 3D organization of the CNS and can be explored taking advantage of many techniques. Here, we review the use of organotypic cultures as a reliable and well defined method to study the mechanisms of neurogenesis under normal and pathological conditions. As an example, we will focus on the possibilities these cultures offer to study the pathophysiology of diseases like Alzheimer disease, Parkinson’s disease, and cerebral ischemia.